Cannabinoid Receptors Modulate Neuronal Morphology and AnkyrinG Density at the Axon Initial Segment - Tapia, Mónica (Front Cell Neurosci, 2017)
Neuronal polarization underlies the ability of neurons to integrate and transmit information. This process begins early in development with axon outgrowth, followed by dendritic growth and subsequent maturation. In between these two steps, the axon initial segment (AIS), a subcellular domain crucial for generating action potentials (APs) and maintaining the morphological and functional polarization, starts to develop. However, the cellular/molecular mechanisms and receptors involved in AIS initial development and maturation are mostly unknown. In this study, we have focused on the role of the type-1 cannabinoid receptor (CB1R), a highly abundant G-protein coupled receptor (GPCR) in the nervous system largely involved in different phases of neuronal development and differentiation. Although CB1R activity modulation has been related to changes in axons or dendrites, its possible role as a modulator of AIS development has not been yet explored. Here we analyzed the potential role of CB1R on neuronal morphology and AIS development using pharmacological and RNA interference approaches in cultured hippocampal neurons. CB1R inhibition, at a very early developmental stage, has no effect on axonal growth, yet CB1R activation can promote it. By contrast, subsequent dendritic growth is impaired by CB1R inhibition, which also reduces ankyrinG density at the AIS. Moreover, our data show a significant correlation between early dendritic growth and ankyrinG density. However, CB1R inhibition in later developmental stages after dendrites are formed only reduces ankyrinG accumulation at the AIS. In conclusion, our data suggest that neuronal CB1R basal activity plays a role in initial development of dendrites and indirectly in AIS proteins accumulation. Based on the lack of CB1R expression at the AIS, we hypothesize that CB1R mediated modulation of dendritic arbor size during early development indirectly determines the accumulation of ankyrinG and AIS development. Further studies will be necessary to determine which CB1R-dependent mechanisms can coordinate these two domains, and what may be the impact of these early developmental changes once neurons mature and are embedded in a functional brain network.